Socialization of the Importance of Household Organic Waste Management into Compost Fertilizer in Wirolegi Village - Vernanda, Rike Intan; Putri, Inge Wiliandani Setya; Wardoyo, Arik Aguk; Maulina, Adilla Dwi Intan; Nurisma, Vani; v, Della Putri; Ramadhani, Adinda Putri; A’yuniya, Shofia (International Journal of Education, Information Technology, and Others, 2024)
Managing household waste, especially organic waste, is still a challenge in Indonesia. The low level of public awareness in processing organic waste into compost causes the accumulation of waste which has a negative impact on the environment. Housewives as the main managers of household waste have an important role in starting the process of managing organic waste independently. This research aims to provide outreach to housewives in RT 001/RW 001, Sumberketangi Environment about how to process organic waste into compost through an educational approach. The methods used include counseling, direct demonstrations, and assistance to housewives in the process of making compost. The results of the activity show an increase in understanding and skills of housewives in managing organic waste. Apart from that, the application of compost in the household environment has been proven to reduce the volume of waste and improve the quality of plants in the home yard. It is hoped that this program can contribute to community-based waste management and encourage environmentally friendly behavior in Wirolegi Village.